CANVA APPLICATION FOR FIQH LEARNING SUBJECTS IN GRADE VAT SDI MATSARATUL HUDA PANEMPAN PAMEKASAN - Moh. Mahfud; Nur Kholis; M Yunus Abu Bakar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the development of a Canva application audio based on visual learning media in the Fiqh learning material in the fifth grade at SDI Matsaratul Huda Panempan Pamekasan. The method used in the research is a developmental research approach, which consists of initial analysis, material identification, product development, and testing. After the product was developed, the feasibility assessment was carried out by the expert to evaluate the media design, content alignment, design completeness, and attractiveness. The expert assessment results show that audio-visual learning media design based on Canva obtained a score of 83 percent in the good category. Limited students’ feedback also indicates a score of 77,13 percent with the good category. Based on theassessments from experts and students, it can be concluded that this Canva-based audio-visual learning media is suitable for use in the experimental school. The field trial results indicate a score of 66.25 percent in the first cycle and 81 percent in the second cycle. The increased percentage of students’ learning outcomes shows that they better understand Fiqh learning material by applying audio-visual learning media based on the Canva application, which has good criteria. Therefore, this developed media can be applied, either in online or offline learning